Unexpected Metal-Free Fluorination and Oxidation at the C-4 Position of Pyrazoles Promoted by Selectfluor - Bonacorso, Helio G.; Pittaluga, Everton P.; Porte, Liliane M. F.; Libero, Francieli M.; Junges, Andrizia F.; Zanatta, Nilo; Martins, Marcos A. P. (Synlett, 2015)
Metal-free electrophilic fluorination, promoted by Selectfluor, of pyrazoles with methylene groups (CH2X), in which X = OH, OMe, F, N3, and NHMe at the C-4 position furnished the 4-fluoro-pyrazole products from unexpected C–C bond cleavage, at moderate to good yields. Otherwise, under the same reaction conditions, when X = NEt2 or SPr, the oxidation product 4-formyl-pyrazole was obtained.
Keywords: electrophilic fluorination; oxidation; Selectfluor; metal-free; pyrazole; hydrazine; Vilsmeier–Haack